Inovasi Model dan Strategi Pembelajaran pada Mata Pelajaran Fiqih Kelas XI dI MAUWH Bahrul Ulum Tambakberas Jombang - Ahmad Nasrullah; Mohammad Saat Ibnu Waqfin (ISLAMIKA, 2023)
Given the importance of updating learning models and strategies in the world of education to suit the digital era, this is one of the supporting factors to continue to spur new innovations in learning models and strategies. so it becomes an answer with time. in educational institutions. Often the learning models and strategies applied by teachers use monotonous learning models, especially in fiqh subjects. It is necessary for teachers to have new innovations in learning models and strategies so that students understand fiqh problems which always increase over time. The refore this study aims to: 1) find out the innovation of learning models and their application to class XI fiqh subjects. 2) to find out the innovative learning strategies and their application to class XI fiqh subjects. 3) to find out the supporting factors in model innovation and learning strategies in class XI fiqh subjects at MAUWH. In this study, the researcher took the title "Innovation of models and learning strategies in class XI fiqh subjects at MAUWH". The method in this study uses descriptive qualitative research. Data collection techniques in this study using observation techniques, interviews and documentation. The types and sources of data used are primary and secondary data by analyzing data validity techniques. The results of this study show that teachers at MAUWH describe model innovations and learning strategies in fiqh subjects that can be used in various ways, with various models and strategies as well as supporting factors. That Innovation Models and learning strategies can be created by updating some or all of the components of learning models and strategies by updating or replacing them by creating new models and strategies by analyzing existing models and strategies.